Relationship between quality in accounting information and organizational characteristics of the third sector entities - Maciel Ramos, Fernando; Klann, Roberto Carlos (Organizações & Sociedade, 2019)
This study aims at evaluating the relationship existing between the quality in accounting information and the organizational characteristics of third sector entities. The methodological design is characterized as a descriptive, documental and quantitative approach. The universe of the study is composed of third sector organizations, formally constituted in the Brazilian scenario. The target population has included organizations with OSCIPS and UPF specification. At the time of the study, 18,553 entities were investigated. The work was based on the probabilistic sample of 392 entities. The results indicate a predominance of the institutions established under the legal form of association. As for size, the foundations have become larger. Regarding the quality of accounting information, we have identified a lower information reported quality index when compared to the second sector. Finally, the results showed that the organizational characteristics of size, creation time and qualification as OSCIP have significant and positive influence on the quality of accounting information of the analyzed entities. It is concluded that the non-profit organizations and regulatory organs need to evolve regarding the accounting information reporting process, as well as the awareness of the importance of these reports for the decision-making process and public accountability.